RENDAHNYA MINAT BELAJAR SISWA PADA MATERI INTI MASALAH EKONOMI KELAS X IPS SMA NEGERI 1 SOSOPAN - Hasibuan, Mistap Rawati (LPPM Universitas Nias Raya, 2024)
This research aims to evaluate the effectiveness of implementing a problem-based learning model in enhancing questioning skills among students of class X IPS at SMA N 1 Sosopan, who were previously observed to be less active and interested in economics learning. The research method employed is classroom action research consisting of two cycles. The research process includes planning, implementation, observation, and reflection. Data was collected through observation of student activities during the learning process. The research findings indicate an improvement in students' questioning skills from Cycle I to Cycle II. In Cycle I, only 9 students or approximately 36% were actively asking questions, while in Cycle II, this number increased to 13 students or around 52%. This suggests that problem-based learning successfully enhances students' questioning skills, with more than 60% of students demonstrating adequate questioning abilities in Cycle II. Therefore, it can be concluded that problem-based learning is effective in increasing interaction and engagement among students in economics learning in the classroom.